Contribution of dry forest products to household income and determinants of forest income levels in the northwestern and southern lowlands of Ethiopia - Teshome, B.; Kassa, H.; Mohammed, Z.; Padoch, Christine (Scientific Research Publishing, Inc., 2015)
Dry forests are dominant vegetation types in East Africa. The contribution of these resources to local livelihoods is poorly understood. This study was conducted to quantify the contribution of dry forest products to household income and to identify factors that influence forest income level in the northwestern and southern lowlands of Ethiopia. Data was collected using key informant interviews, focus group discussions and formal survey administered to 428 randomly selected households from representative districts in three regional states. Regression analysis, one way ANOVA, chi-square and t-tests were used to analyze the quantitative data. The major sources of household income are crop production, livestock farming, forest products, off- and non-farm activities, and remittances and aid, contributing respectively to 46.3%, 27.6%, 17.0%, 6.3% and 2.8% of the household income. The relative importance of forest income to total household income varied significantly across wellbeing categories (P < 0.001), representing 31.8%, 15.5% and 9.9% respectively for poor, medium and rich households and also between male headed (16.1%) and female headed (23.5%) households(P < 0.001). In terms of magnitude, however, forest income differed significantly (P < 0.05) with wealth category of households but not with the gender of the household head. Forest income level was significantly and positively influenced by family size (P < 0.01) and being a member of gums and resins producers cooperative (P < 0.01), while distance to the forest resource (P < 0.01) and being in Tigray or Amhara Regional States (Oromia being reference state) negatively and significantly affected forest income levels of households. Attempts to promote sustainable management of dry forests should recognize these factors that influence access to forests and forest income level of different members of the community to ensure equitable responsibility and benefit sharing arrangements and inclusive participation for better livelihoods and conservation outcomes.